Critical thinking dimensions as predictors of scientific argumentation skills among prospective elementary school teachers - Siti Ni’matul Fitriyah; Zuni Mitasari; Moh. Farid Nurul Anwar; M. Rifa’i (JPBI (Jurnal Pendidikan Biologi Indonesia), 2026)
Background: Scientific argumentation is an essential competence in science education because it requires students to evaluate evidence, justify claims, and construct evidence-based reasoning. These processes are closely associated with critical thinking. Objectives: This study examined the associations between six critical thinking dimensions; interpretation, analysis, evaluation, inference, explanation, and self-regulation and students’ scientific argumentation skills, and identified which dimensions significantly predicted scientific argumentation in a Basic Science course. Methods: A quantitative correlational design was employed with 95 prospective elementary school teachers selected through purposive sampling. Data were collected using instruments assessing the six dimensions of critical thinking and scientific argumentation skills and analyzed using multiple linear regression. Results: Collectively, the six critical thinking dimensions were significantly associated with scientific argumentation skills and explained 88.9% of the variance in the regression model. Evaluation and explanation were significant positive predictors of scientific argumentation, whereas interpretation, analysis, inference, and self-regulation did not make statistically significant unique contributions after accounting for the other dimensions in the model. Explanation emerged as the strongest predictor. Conclusion: The findings demonstrate a strong association between critical thinking dimensions and scientific argumentation, with evaluation and explanation emerging as the strongest predictors. These findings underscore the importance of fostering evidence evaluation, claim justification, and scientific explanation in science teacher education.